Pedigree growth strategy (A) - Calkins, Tim; Deming, Ann (London : SAGE Publications Ltd, 2017)
Julie Smith, brand manager for dog food manufacturer Pedigree, has to determine how best to jump-start growth in the slumping business. The (A) case centers on the debate over which type of strategy to pursue, brand building versus in-store activity, while the (B) case focuses on the concept of cause marketing as a growth strategy.
Originally published: Calkins, T., & Deming, A. (2010). Pedigree growth strategy (A). 5-110-010(A). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Pedigree Petfoods (Firm) -- Case studies; Pet food industry -- United States -- Case studies; Corporations -- United States -- Growth -- Case studies; Business planning -- Case studies